Comparing the association of two metabolic syndrome definitions, NCEP ATP III and IDF, with the risk of developing atherosclerotic cardiovascular disease: An analytical cross‐sectional study - Gholamreza Yousefzadeh; Amin Sayyadi; Hamid Najafipour; Vida Sabaghnejad; Sara Pezeshki (Endocrinology, Diabetes & Metabolism, 2024)
Abstract Introduction Atherosclerotic cardiovascular diseases (ASCVD) are significant sources of mortality and morbidity with substantial economic implications and preventive measures play key roles in this regard. Metabolic syndrome (MetS) is a common condition, and its association with ASCVD and mortality has made it clinically important. However, controversies persist regarding the best definition for MetS. Here in, we investigated the ability of the International Diabetes Federation (IDF) and the National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III) in the prediction of ASCVD incidence. Methods We conducted an investigation on individuals diagnosed with MetS as part of the “Kerman Coronary Artery Diseases Risk Factor Study” (KERCADRS). This study was a cohort study conducted on a population aged 15–75 years residing in Kerman, Iran to assess the risk of ASCVD. We employed ACC/AHA ASCVD Risk Estimator for predicting ASCVD occurrence in the future and then compared the results with different definitions of MetS including IDF and NCEP ATP III. Results Patients with MetS consistent with NCEP ATP III had higher ASCVD risk scores than those with IDF (10.63 ± 10.989 vs. 9.50 ± 9.357). NCEP ATP III had better overall performance in terms of specificity, accuracy, sensitivity and positive and negative predictive values especially in higher ASCVD risk score categories. The agreement between IDF and NCEP ATP III was none to slight (Cohen's Kappa <0.2) except for IDF in the group of ASCVD >30%, which revealed no agreement (Cohen's Kappa = 0). Conclusion NCEP ATP III has better overall performance compared to IDF. The ability of NCEP ATP III increases as the ASCVD risk score goes higher. IDF may be useful in primary screening and patients with lower ASCVD risk scores.